Use Cases of the Integrated Administration and Control System's Plot-Level Data: Protocol and Pilot Analysis for a Systematic Mapping Review - Heidi Leonhardt; Silke Huẗtel; Tobia Lakes; Maximilian Wesemeyer; Saskia Wolff (German Journal of Agricultural Economics (GJAE), 2023)
In recent years, land use data from the EU's Integrated Administration and Control System (IACS) have become increasingly available for research purposes. IACS data contain annual plot-level information on cultivation and location of the land farmed by agricultural beneficiaries, covering the majority of farmland in the EU. The data thus provide information on land use that is spatially and temporally highly disaggregated. Researchers from a broad range of disciplines already rely on IACS data for various applications and EU member states must make an anonymised, geospatially-referenced version of the data publicly available in the future. However, there is no complete and structured overview of the data's use, their benefits and limitations that future research could rely on. This calls for conducting a systematic review of the applications of IACS plot-level data in scientific literature. Preparing the ground for such a review, this paper presents a review protocol for identifying and analysing publications using plot-level IACS data from Austria, Czechia, France, Germany, and Sweden in a systematic map. To test and refine the protocol and to illustrate the planned review, we conduct a pilot analysis of 12 selected academic publications and present the results. The pilot analysis demonstrates that the review protocol is adequate and that novel insights will be gained by mapping out the already existing work that uses IACS data.
Keywords: 330